2019
DOI: 10.3389/fonc.2019.00675
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery for Breast Reconstruction: Pooled Meta-Analysis of 10 Observational Studies Involving 1,838 Patients

Abstract: Purpose: This study aims to explore the effectiveness and safety of the enhanced recovery after surgery (ERAS) protocol vs. traditional perioperative care programs for breast reconstruction. Methods: Three electronic databases (PubMed, EMBASE, and Cochrane Library) were searched for observational studies comparing an ERAS program with a traditional perioperative care program from database inception to 5 May 2018. Two reviewers independently screened the literature according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…They reported an increase in abdominal complications in their enhanced recovery protocol group due to early mobilisation -36% vs 51% 27 . This similar to the findings of a recent systematic review 8 . In contrast, we had very low rate of abdominal wound infection (2/28) and no incidence of delayed wound healing at the donor site.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…They reported an increase in abdominal complications in their enhanced recovery protocol group due to early mobilisation -36% vs 51% 27 . This similar to the findings of a recent systematic review 8 . In contrast, we had very low rate of abdominal wound infection (2/28) and no incidence of delayed wound healing at the donor site.…”
Section: Resultssupporting
confidence: 91%
“…A key aim of enhanced recovery protocols (ERAS) is reducing the length of hospital stay. Recent publications of enhanced recovery protocols from well-established large volume centres have demonstrated a median length of stay between 4-7 days [4][5][6][7][8][9][10][11]26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results concur with other meta-analysis studies on the ERAS program. Tan et al ( 35 ) on breast reconstruction, Malczak et al ( 34 ) on bariatric surgery, Zhuang et al ( 13 ) on colorectal surgery; have all demonstrated that implementation of ERAS leads to significantly reduced LOS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ERAS pathways in microvascular breast reconstruction have been shown to reduce opioid use and improve pain control as compared with traditional postsurgical pathways. 35,36 It is unclear if the effects of lavender aromatherapy may be more pronounced in the absence of the perioperative multimodal pain regimens seen in conjunction with ERAS pathways.…”
Section: Discussionmentioning
confidence: 99%